An Interdisciplinary Pain Rehabilitation Program for Veterans with Chronic Pain: Description and Initial Evaluation of Outcomes - Nidhi S. Anamkath; Sarah A. Palyo; Sara C. Jacobs; Alain Lartigue; Kathryn Schopmeyer; Irina A. Strigo (Pain Research and Management)
Objective. Chronic pain conditions are prominent among Veterans. To leverage the biopsychosocial model of pain and comprehensively serve Veterans with chronic pain, the San Francisco Veterans Affairs Healthcare System has implemented the interdisciplinary pain rehabilitation program (IPRP). This study aims to (1) understand initial changes in treatment outcomes following IPRP, (2) investigate relationships between psychological factors and pain outcomes, and (3) explore whether changes in psychological factors predict changes in pain outcomes. Methods. A retrospective study evaluated relationships between clinical pain outcomes (pain intensity, pain disability, and opioid use) and psychological factors (depressive symptoms, catastrophizing, and “acceptable” level of pain) and changes in these outcomes following treatment. Multiple regression analysis explored whether changes in psychological variables significantly predicted changes in pain disability. Results. Catastrophizing and depressive symptoms were positively related to pain disability, while “acceptable” level of pain was idiosyncratically related to pain intensity. Pain disability and psychological variables showed significant changes in their expected directions. Regression analysis indicated that only changes in depressive symptoms significantly predicted changes in pain disability. Conclusion. Our results are consistent with evidence-based clinical practice guidelines for the management of chronic pain in Veterans. Further investigation of interdisciplinary treatment programs in Veterans is warranted.